The Influence of Multiple Role Conflicts and Work Stress on Job Satisfaction and Its Implications for Employee Performance in BPS Environment of West Java Province - Kwik Singgih Santoso; Anoesyirwan Moeins (Journal of Accounting and Finance Management, 2021)
The performance achievements of BPS employees for the period 2017 to 2021, the results show that there has been a decrease in the performance achievements of BPS employees in 2021 compared to the previous year. This performance achievement component contains several key performance indicators, including indicators aimed at increasing the capacity of human resources (HR) and institutional arrangements. In order to maintain the quality and commitment of BPS employees in West Java Province, they are required to achieve the targets given. Therefore, it must be considered factors that can affect performance such as multiple role conflict, job stress and satisfaction. This study aims to analyze the effect of multiple role conflict and work stress on job satisfaction and its implications for employee performance in the BPS environment of West Java province. This study uses multiple regression analysis methods and SPSS 26 software to measure the effect of multiple role conflict and job stress on Job Satisfaction and the Implications for Employee Performance in the BPS Environment of West Java Province. The type of research used is descriptive and verification. The research method used is a case study. Data collection techniques using questionnaires, interviews and observation. The research population is employees in the West Java Province BPS environment as many as 101 people who are used as samples. The results showed that there was a significant negative effect of Dual Role Conflict on job satisfaction and there was a negative and insignificant effect of work stress on satisfaction and there was an effect of Multiple Role Conflict, job stress and job satisfaction on employee performance either partially or simultaneously. This means that the existence of Multiple Role Conflicts and work stress will reduce job satisfaction of BPS West Java Province employees which will have an impact on employee performance results.